Validity, Reliability and Responsiveness of the Malay Shoulder Pain and Disability Index (M-SPADI) for Patients with Shoulder Pain - Abdul-Karim S; Abdul-Hamid MS; Ho CA; Ling JCY (Malaysian Orthopaedic Journal, 2023)
Introduction: The purpose of this study is to determine the validity, reliability, and responsiveness of the Malay Shoulder Pain and Disability Index (M-SPADI) in Malay speakers suffering from shoulder pain. Materials and methods: The M-SPADI, the Numerical Rating Scale (NRS), and measurements of shoulder active range of motion (AROM) were completed by 140 patients with shoulder pain (68 with rotator cuff pathology and 72 with other shoulder pathology). Thirty-four patients were retested for test-retest reliability with M-SPADI after an average of 9.2 days. M-SPADI was performed on twenty-one individuals three months after completing treatment for rotator cuff disorders to assess response. Results: The results of exploratory factor analysis revealed a bidimensional structure for M-SPADI. M-SPADI disability score was significantly greater in patients with rotator cuff pathologies (median = 31.87, IQR 82.50) than in patients with other shoulder pathologies (median = 20.00, IQR 23.84). In multi-group factor analysis, measurement invariance revealed no significant difference between the two groups (p>0.05). There was a significant positive correlation between M-SPADI and NRS (Pain = 0.86, Disability = 0.75, Total = 0.82, p=0.005), and a significant negative correlation between M-SPADI and shoulder AROM (Pain = -0.34 to -0.67, Disability =-0.44 to -0.73, Total =- 0.43 to -0.72, p=0.005). M-SPADI had a high degree of internal consistency (Cronbach's 0.92 for pain and 0.95 for disability). Test-retest reliability was moderate to excellent (ICC Pain = 0.84, ICC Disability = 0.78, ICC Total = 0.81, p=0.001), and the smallest detectable change ranges (Pain = 8.74, Disability = 3.21, Total = 3.83) were less than the minimal detectable change ranges (Pain = 21.57, Disability = 6.82, Total = 8.79). The area under the receiver operating characteristic curve (AUC) for M-SPADI was greater than 0.90 (Pain = 0.99, Disability = 0.94, Total = 0.96). Conclusion: The M-SPADI has established construct validity, internal consistency, test-retest reliability, and responsiveness. The M-SPADI is a reliable and valid instrument for evaluating shoulder pain among Malay- speaking individuals. In addition, the M-SPADI disability subscale may be useful for monitoring functional score changes in patients with rotator cuff pathology.